Pengaruh Pengawasan Kinerja Terhadap Produktivitas Kerja pada Biro Umum di Badan Narkotika Nasional - Elhuloqo, Ihsana; Hidayat, Ahmad Dzaki (Utilitas, 2017)
This research intended to measure the effect of performance supervision toward the staff’s productivity of General Bureau Division of Badan Narkotika Nasional (National Antinarcotics Agency) of Indonesia. The disproportionate stratified random sampling technique used to choose 74 staffs as research’s samples. The associative quantitative method applied for this sresearch. The test of normality and homogenity of data conducted to test the data distribution normality, and continued by Analysis of Variance Test. The linear regression calculation summarized that ȳ = 34.467 + 0.674 (x) and ANAVA test result was Fcount < Ftable (1.62 < 1.80). The hipothesis tested by Pearson’s product moment correlation test to gain rxy = 0.600, it means that there was a strong effect of performance supervision toward staffs’ productivity as measured by interpretation criteria of the coefficient correlation interpretation table. So, the paper concluded that there is an effect of performance supervision toward staff’s productivity. Keywords: Performance supervision, Job’s productivity, associative quantitative method